PERANAN MAHASISWA KKN DALAM PENINGKATAN LITERASI - Maria Augustin Lopes Amaral; Jesica Mirna Aprilia; Afrianus Jenudin; Anselmus Boy Baunsele; Erly G. Boelan (Politeknik Negeri Sriwijaya, 2023)
Students' interest in learning has decreased coupled with the Covid-19 situation, which has made students study alone at home; teachers need to improve literacy skills in current students. The presence of Widya Mandira Catholic University's KKNT-PPM students helped overcome this problem by teaching in class using visual aids at SDK Halilulik for a month. The activity begins with observation and implementing activities in the Halilulik SDK classroom. Teaching aids help teachers to close gaps and hone students' literacy comprehension skills. Using teaching aids, youtube, TikTok, magazines, and comics are appropriate teaching aids that help in helping students understand a topic in class. Opinions from teachers and parents that children become more understanding and enthusiastic about learning after being brainwashed by KKN students using visual aids. The hope for the future is that activities like this can take place continuously.